Environmental and Ecological Approach in the Restoration of Historical Monuments. Issue 1 (1st December 2022) - Al Adgham, S.; Saba, M.; Sabalbal, G.; Arairo, W.; Absi, J.
Abstract: Architectural heritage preservation requires more attention to save historical monuments as it protects the distinctiveness of the country. However, large portions of construction and demolition waste come from the renovation sector. As such, the need for eco-friendly materials is a necessity to decreasing the environmental impact of renovation processes such as the carbon footprint and global warming. The study aims to use geopolymeric paste as a potential alternative for renovating architectural elements in Al-Attar Mosque, Tripoli, instead of cementitious materials that impact the environment. The mix design of the geopolymer paste consists of metakaolin and sodium-based alkaline solution. The paste is used to bind very old sandstone rocks provided by the historic mosque. The mechanical properties of the natural sandstone were tested with and without geopolymeric paste in different cutting conditions. In most of the samples, the cracking occurred in the stone itself and not in the geopolymer binder. This behaviour proved that the geopolymer binder is a good alternative to be used in renovating the wall, holding good mechanical properties. As such, it proved that it has good potential to be used in historical monuments. It is also an environmentally friendly material, with a lower carbon footprint than concrete.